2010
DOI: 10.1590/s0037-86822010000600005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use and incidence of multidrug-resistant Pseudomonas aeruginosa in a teaching hospital: an ecological approach

Abstract: Introduction: Multidrug-resistant Pseudomonas aeruginosa is a major threat in healthcare settings. The use of antimicrobials can influence the incidence of resistant strains by direct and indirect mechanisms. The latter can be addressed by ecological studies. Methods: Our group attempted to analyze the relation between the use of antipseudomonal drugs and the incidence of MDR-PA among 18 units from a 400-bed teaching hospital. The study had a retrospective, ecological design, comprising data from 2004 and 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…aeruginosa emerged as an important pathogen and was reasonable for nosocomial infections. So, that is one of the important causes of morbidity and mortality among Hospital patients [3] [4] [19]. The current study showed that P. aeruginosa was highly prevalent in clinical samples of urine and pus, was also observed in Arshi, et al and Murase et al study [20] [21].…”
Section: Discussionsupporting
confidence: 63%
“…aeruginosa emerged as an important pathogen and was reasonable for nosocomial infections. So, that is one of the important causes of morbidity and mortality among Hospital patients [3] [4] [19]. The current study showed that P. aeruginosa was highly prevalent in clinical samples of urine and pus, was also observed in Arshi, et al and Murase et al study [20] [21].…”
Section: Discussionsupporting
confidence: 63%
“…The root causes of the rapid emergence and dissemination of drug-resistant bacteria in hospitals are multifactorial 2,29,30 , including mainly the high selective pressure that results from inappropriate and widespread use of antimicrobial agents particularly in ICUs; cross transmission from patient to patient owing to inconsistent application of appropriate infection control measures; clonal spreading of resistant bacteria and horizontal transfer of resistance genes; and a complex relationship between resistance and use of a variety of antimicrobials 2,29,31 . However, increasing resistance may further drive increased consumption of several so-called last-line antimicrobial agents 2 .…”
Section: Relationship Between Antibiotic Consumption and Resistancementioning
confidence: 99%
“…Interest in Pseudomonas aeruginosa detection has emerged in response to the prevalence of this organism and its status as a clinically important, opportunistic pathogen that infects hosts with compromised immune systems [4,5], which alone is responsible for ca. 15 % of all nosocomial infections in Brazil [1,[6][7][8][9]. Bacterial migration is important in understanding many practical problems ranging from disease pathogenesis to the bioremediation of hazardous wastes in the environment [10,11].…”
Section: Introductionmentioning
confidence: 99%